Immediate Hire or Immediate Rejection? : Grammar Usage Errors Taint Ratings of Applicants’ Writing, Employability, and Character - Paulich, Katie; Shafer, Paige; Kofman, Chloe; Richmond, Caitlin; Bleske-Rechek, April A. (My University, 2018)
Scholars debate whether English instructors should devote focused attention to grammar usage and mechanics. On one hand, most grammar usage errors are superficial and do not impede readers’ understanding, and an emphasis on mastery of usage rules perpetuates a system in which certain forms of grammar usage may afford status and prestige. On the other hand, studies have illustrated that professionals perceive grammar usage errors as bothersome; more importantly, interviews with business professionals suggest that grammar usage errors might harm impressions of the writer as a person.
Color poster with text and graphs.
Keywords: Questionable grammar usage; Employee selection; Personality judgement; Posters